Determinants of Automotive Sub-Sector Profitability: A 2017-2020 Analysis on Indonesian Stock Exchange: Penentu Profitabilitas Sub-Sektor Otomotif: Analisis Tahun 2017-2020 pada Bursa Efek Indonesia - Ainun Najib; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of liquidity, capital structure, firm size, and effective tax rate on the profitability of companies within the automotive sub-sector listed on the Indonesian Stock Exchange from 2017 to 2020. Employing purposive sampling, a sample of 12 companies was selected, and secondary data were analyzed using multiple linear regression. The findings reveal that liquidity, capital structure, firm size, and effective tax rate each individually influence profitability within the automotive sub-sector. Furthermore, when considered together, these factors exhibit a simultaneous impact on profitability. These results contribute to a deeper understanding of the financial dynamics within the automotive industry, offering valuable insights for practitioners, policymakers, and researchers in the global context. Highlight: Comprehensive Analysis: This study examines the impact of key financial factors on automotive sub-sector profitability. Strategic Sample Selection: Purposive sampling ensures a focused and representative sample of 12 companies. Holistic Insights: The study's combined findings shed light on the simultaneous influence of liquidity, capital structure, firm size, and effective tax rate, enhancing our understanding of the automotive industry's financial dynamics. Keywords: Liquidity, Capital Structure, Firm Size, Effective Tax Rate, Automotive Sub-Sector Profitability.